( 3 lo g 4 ( lo g 3 x ) ) ( 2 lo g 6 4 ( lo g 3 x ) − 1 ) = − 1
Find the sum of all the positive integers x satisfying the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let lo g 3 x = 4 3 y . Then by substitution:
3 lo g 4 ( lo g 3 x ) ( 2 lo g 6 4 ( lo g 3 x ) − 1 ) = − 1
3 lo g 4 4 3 y ( 2 lo g 6 4 4 3 y − 1 ) = − 1
3 ⋅ 3 y ⋅ ( 2 ⋅ y − 1 ) = − 1
1 8 y 2 − 9 y + 1 = 0
( 3 y − 1 ) ( 6 y − 1 ) = 0
3 y = 1 or 6 y = 1
If 3 y = 1 , then:
lo g 3 x = 4 3 y
lo g 3 x = 4 1
x = 3 4 = 8 1
If 6 y = 1 , then 3 y = 2 1 and:
lo g 3 x = 4 3 y
lo g 3 x = 4 2 1
x = 3 2 = 9
Therefore, the sum of the two solutions for x is 8 1 + 9 = 9 0 .
Problem Loading...
Note Loading...
Set Loading...
Let u = l o g 4 ( l o g 3 x ) and let us rewrite the above equation as:
3 u ( 2 ⋅ l o g 4 ( 6 4 ) u − 1 ) ⇒ 3 u ( 3 2 u − 1 ) = − 1 ;
or 2 u 2 − 3 u + 1 = 0 ;
or ( 2 u − 1 ) ( u − 1 ) = 0 ;
or u = 2 1 , 1 .
Now we substitute back to obtain: l o g 4 ( l o g 3 x ) = 2 1 , 1 ⇒ l o g 3 x = 2 , 4 ⇒ x = 9 , 8 1 . Hence, the sum of all such x equals 9 + 8 1 = 9 0 .